Effects of plyometric training on endurance and explosive strength performance in competitive middle- and long-distance runners - Ramirez-Campillo, R.; Álvarez, C.; Henriquez-Olguin, C.; Baez, E. B.; Martinez, C.; Andrade, D. C.; Izquierdo, M. (The Journal of Strength and Conditioning Research, 2014)
The purpose of this study was to examine the effect of a short-term plyometric training program on explosive strength and endurance performance in highly competitive middle- and long-distance runners. Athletes were randomly assigned to a control group (CG, n = 18, 12 men) and an explosive strength training group (TG, n = 18, 10 men). Drop jump (DJ) from 20 (DJ20) and 40 cm (DJ40), countermovement jump with arms (CMJA), 20-m sprint time, and 2.4-km endurance run time test were carried out before and after 6 weeks of explosive strength training. Also, the combined standardized performance (CSP) in the endurance and explosive strength test was analyzed. After intervention, the CG did not show any significant change in performance, whereas the TG showed a significant reduction in 2.4-km endurance run time (-3.9%) and 20-m sprint time (-2.3%) and an increase in CMJA (+8.9%), DJ20 (+12.7%), and DJ40 (16.7%) explosive performance. Strength training group also exhibited a significant increase in CSP, although the CG showed significant reduction. We conclude that properly programmed concurrent explosive strength and endurance training could be advantageous for middle- and long-distance runners in their competitive performance, especially in events characterized by sprinting actions with small time differences at the end of the race.